A Review of Gerotor Technology in Hydraulic Machines - Pedro Javier Gamez-Montero; Esteve Codina; Robert Castilla (Energies, 2019)
Over the years, numerous investigations have established the gerotor fundamentals. This work aims to provide a complete review of the literature from the last decade, focusing on the articles published in the past five years on gerotor technology in hydraulic machines. The report gives a catalogue of guidelines based on the trochoidal-envelope definition, a background analysis, the worldwide distribution of articles in each continent and country and the most frequently used keywords in the field. The paper identifies state-of-the-art research, and reports on current mainstream ideas. From the historical background, this literature review reports the current approaches in gerotor pumps (geometry and performance approaches, modeling and numerical simulations), orbital motors and new concepts. The report will serve as a guide and a directory for novel engineers working with gerotor technology in hydraulic machines. Another intention of this paper is to disseminate the works of the researchers who use this technology around the world, and to provide a scenario for future international collaboration. The paper gives an account of the disparity between academia and engineering applications. There is currently very little published literature on design and production methodologies for gerotor pumps and orbital motors. Hence, the future goal is to collect recommendations that combine academia and industry expertise to make better use of these extensive studies in the field.